PENGEMBANGAN AGROWISATA DI CV TANI ORGANIK MERAPI YOGYAKARTA - Wien Kuntari (Fakultas Kehutanan Universitas Winaya Mukti, 2021)
Natural tourism Kaliurang - Yogyakarta is one of the natural tourist destinations that presents natural beauty and agro-tourism which is in great demand by tourists. CV Tani Organic Merapi is a company engaged in organic agriculture and agro-tourism. The purpose of the business development study is to formulate business development ideas based on internal and external factors, and to assess business feasibility. The study method used is SWOT analysis, market and marketing aspects, technical aspects, organizational and management aspects, human resources aspects, collaboration aspects, and financial aspects. The results of the SWOT analysis, namely the W-O strategy: agro-tourism development at CV Tani Organic Merapi, Yogyakarta. Based on non-financial analysis, from the market and marketing aspects, it already has a clear target market. In the production aspect, the activity schedule, operational activity flow and outbound layout have been made. In the organizational and management aspects, there is a structured division of work. Aspects of human resources, the availability of the required workforce. The collaboration aspect includes suppliers for input and cooperation with marketing. From the financial aspect, this business development has an NPV value of Rp. 823,858,056.34, IRR 60 percent, Net B/C 5.38, Gross B/C 1.18, and Payback period of 2 years 7 months. Based on the switching value analysis, there was a 15 percent decrease in visitors. The results of financial and non-financial analysis show that agro-tourism development activities are feasible.